Annotated Bibliography on the Exotic Bivalve Corbicula in North America, 1900–1971 - Ralph M. Sinclair (Hello World!, 1971)
The Asian clam, Corbicula manilensis, is currently the most costly liability of all exotic molluscs in North America. It's range has expanded since about 1938 from the Columbia River, south to Baja California and east to Florida. Its present range still excludes the Great Lakes Basin, the middle and North Atlantic, the Upper Missouri and the upper Mississippi River.